2023
DOI: 10.3390/ijms241814315
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with the Topical Antimicrobial Peptide Omiganan in Mild-to-Moderate Facial Seborrheic Dermatitis versus Ketoconazole and Placebo: Results of a Randomized Controlled Proof-of-Concept Trial

Jannik Rousel,
Mahdi Saghari,
Lisa Pagan
et al.

Abstract: Facial seborrheic dermatitis (SD) is an inflammatory skin disease characterized by erythematous and scaly lesions on the skin with high sebaceous gland activity. The yeast Malassezia is regarded as a key pathogenic driver in this disease, but increased Staphylococcus abundances and barrier dysfunction are implicated as well. Here, we evaluated the antimicrobial peptide omiganan as a treatment for SD since it has shown both antifungal and antibacterial activity. A randomized, patient- and evaluator-blinded tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…This phase separation of the membrane ultimately leads to membrane permeabilization Facial seborrheic dermatitis in phase II Omiganan was safe and well tolerated but did not result in a significant clinical improvement of seborrheic dermatitis when compared to the use of ketoconazole. (ClinicalTrials.gov Identifier NCT03688971) [ 148 ] PAC113 Targets the mitochondrial complex I, increasing free radicals and inhibiting cellular respiration, with a membrane-lytic activity associated Histatin-derived used as a mouth rinse for oral candidiasis Clinical trial ended in 2008, with no results published (ClinicalTrials.gov Identifier NCT0065997) [ 90 , 91 ] CZEN-002 Derived from a melanocyte-stimulating hormone and works as a membrane disruptive agent, as well as disruption of cAMP signaling pathways and immunomodulation, such as the suppression of TNFα production Vulvovaginal candidiasis, phase IIb Relief from vaginal candidiasis with positive results: a phase I/II clinical trial reported 88.2% and 87.5% cure, but no follow-up trial ( https://www.eurekalert.org/news-releases/796451 —accessed October 2023) [ 143 , 147 , 149 , 150 ] …”
Section: Antimicrobial Peptides (Amps)mentioning
confidence: 99%
“…This phase separation of the membrane ultimately leads to membrane permeabilization Facial seborrheic dermatitis in phase II Omiganan was safe and well tolerated but did not result in a significant clinical improvement of seborrheic dermatitis when compared to the use of ketoconazole. (ClinicalTrials.gov Identifier NCT03688971) [ 148 ] PAC113 Targets the mitochondrial complex I, increasing free radicals and inhibiting cellular respiration, with a membrane-lytic activity associated Histatin-derived used as a mouth rinse for oral candidiasis Clinical trial ended in 2008, with no results published (ClinicalTrials.gov Identifier NCT0065997) [ 90 , 91 ] CZEN-002 Derived from a melanocyte-stimulating hormone and works as a membrane disruptive agent, as well as disruption of cAMP signaling pathways and immunomodulation, such as the suppression of TNFα production Vulvovaginal candidiasis, phase IIb Relief from vaginal candidiasis with positive results: a phase I/II clinical trial reported 88.2% and 87.5% cure, but no follow-up trial ( https://www.eurekalert.org/news-releases/796451 —accessed October 2023) [ 143 , 147 , 149 , 150 ] …”
Section: Antimicrobial Peptides (Amps)mentioning
confidence: 99%